Evidence-Based and Stakeholder-Oriented Decision-Making in ‎Organizations: A Conceptual Study on Organizational ‎Effectiveness, Legitimacy, and Sustainability - Saripuddin Daulay (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to examine the conceptual foundations, processes, determinants, and stakeholder implications of organizational decision-making. A qualitative conceptual literature review was employed by synthesizing relevant scholarly literature on management, leadership, organizational behavior, and stakeholder management. The findings indicate that organizational decision-making is not limited to selecting an alternative but involves identifying problems, gathering relevant information, developing and evaluating alternatives, implementing decisions, and assessing outcomes. Decision quality is influenced by information accuracy, leadership competence, organizational culture and structure, resource availability, technological developments, and internal and external environmental conditions. The review also shows that stakeholder-oriented decision-making is essential for strengthening organizational legitimacy, public trust, and support for policy implementation. Conversely, decisions made without adequate information, contextual analysis, and stakeholder consideration may lead to resistance, conflict, inefficiency, and reputational risks. This study concludes that systematic, evidence-informed, participatory, and ethically grounded decision-making is essential for improving organizational effectiveness, responding to uncertainty, and supporting long-term sustainability.